Andrie du Toit (ed), Focusing on the message. New Testament hermeneutics, exegesis and methods - Hermie C. van Zyl (Acta Theologica)
This book is about methods — methods used in understanding the message of the New Testament. But contrary to what one would expect of a textbook on methodology, this book pays scant attention to the historical critical paradigm. It rather focuses on the so-called synchronic methods which deal with the final text of the New Testament. There is one exception though, namely redaction criticism, seemingly because the latter represents a “hybrid” approach consisting of diachronic and synchronic moments; it starts out studying the sources or prehistory of the text, but in doing so it also exposes its final features.